Aerodynamics of Blended Wing Body (BWB) Unmanned Aerial Vehicle (UAV) using Computational Fluid Dynamics (CFD) / Aman Mohd Ihsan Mamat … [et al.] - Mohd Ihsan Mamat, Aman (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
A thorough understanding of the aerodynamic behaviour of Blended Wing Body (BWB) aircraft is important because of its high lift to drag ratio. The use of Computational Fluids Dynamics (CFD) has accelerated aerodynamic analysis of BWB aircraft. Steady-state, three-dimensional CFD calculations were made of the BWB model using the Spalart-Allmaras turbulence model. Comparisons of aerodynamic characteristics such as lift coefficient, drag coefficient, pitching moment coefficient, pressure contours and Mach number contours were made both of two-dimensional aerofoil sections in the BWB model and a complete three-dimensional model. The lift coefficient distributions along the body and wing span were analyzed. The effect of changing the angles of attack and aerofoil profiles were investigated. The BWB design presented here has achieved an unprecedented capability in terms of sustainability of flight at high angle of attack, low parasite drag coefficient, efficient thrust required at optimum flight speed and acceptable margin of centre of gravity for trimmed flight at optimum speed without control surface interference.